Evaluation of cropping sequences of hybrid vegetables for N fertilizer recovery efficiency and utilization of residues using 15N-enriched urea - Kotur, S C; Ramesh, P R; Anjaneyulu, K; Ramachandran, V (The Indian Journal of Agricultural Sciences, 2012)
Among six possible cropping sequences of okra (Abelmoschus esculentus), tomato (Lycopersicon esculentum) and cabbage (Brassica oleracea var. capitata), the sequence ‘cabbage-tomato-okra’ was the most N efficient showing 17.925 kg/plot (1 m × 1.8 m) of fertilizer N uptake and 39.6% recovery of N applied to the first crop, followed by that of ‘cabbage-okra-tomato’ (35.9). Cabbage as the second crop showed the highest recovery of residual fertilizer N of 2.27 – 4.61% compared to other crops. The ability of the crops in the uptake of fertilizer N and therefore the associated fertilizer recovery efficiency was in the order: cabbage> tomato>okra when grown as first and second crops. The recovery of residue by the third crop was meager (0.12– 0.33%). Therefore, the inherent capacity of the component vegetable crop in a cropping sequence to utilize the direct and residual N decides the overall N-use efficiency of the cropping sequence.